An ethics training specific for European public health - Camps, Victoria (Public Health Rev, 2015)
Training in public health ethics is not at the core of public health programmes in Europe. The fruitful progress of the United States could stimulate the European schools of public health and other academic institutions to develop specifically European teaching programmes for ethics that embrace both transatlantic innovations and some adaptations based on the evolution of moral values in European societies. This paper reviews the arguments for a European public health ethics curriculum and recommends the main features of such a programme. Europe shares common values and, above all, the three major ethical principles that were socially and politically crystallized by the French Revolution: liberty, equality, and fraternity. Fraternity, otherwise known as solidarity, although rarely mentioned in the literature on ethical issues, is the moral value that best defines the European concept of public health expressed as a common good, mutual aid, and a collective or shared responsibility for health of the population. Specific political motivations were responsible for the origin of European health systems and for current policy proposals led by the European Union, such as Europe’s commitments, at least in theory, to: reduce social inequities in health and to develop the health in all policies approach. These and other initiatives, albeit not exclusively European, have political and legal repercussions that pose unique ethical challenges. Europe combines homogeneity in social determinants of health with heterogeneity in public health approaches and interventions. It is therefore necessary to develop training in ethics and good government for all public health workers in Europe, especially since a large segment of the population’s health depends on actions and decisions adopted by the European Commission and its regulatory agencies as well as for non EU European Region countries. Based on these arguments, the paper concludes with several recommendations for a common nucleus for the ethics curriculum in Europe.